Pneumococcal carriage among children after four years of routine 10-valent pneumococcal conjugate vaccine use in Brazil: The emergence of multidrug resistant serotype 6C. Issue 21 (15th May 2017) - Neves, Felipe P.G.; Cardoso, Nayara T.; Snyder, Robert E.; Marlow, Mariel A.; Cardoso, Claudete A.A.; Teixeira, Lúcia M.; Riley, Lee W.
Highlights: Effects of PCV10 on carriage were evident after 4 years of routine vaccination. Demographic and clinical characteristics associated with carriage were described. PCV10 serotypes were virtually eliminated. High non-susceptibility rates (>20%) to several antibiotics were observed. Multidrug resistant serotype 6C isolates emerged. Abstract: Background: In 2010, the 10-valent pneumococcal conjugate vaccine (PCV10) was introduced free of charge in Brazil as part of the public immunization program. Here we investigated the carriage prevalence, colonization risk factors, capsular types, and antimicrobial resistance among pneumococcal isolates obtained from children in Brazil four years after routine PCV10 use. Methods: Between September and December 2014, we conducted a cross-sectional study among children < 6 years old who attended one public and two private clinics in Niterói, RJ, Brazil to evaluate pneumococcal nasopharyngeal carriage. Antimicrobial susceptibility and capsular types were determined for all isolates. Results: Of 522 children, 118 (22.6%) were pneumococcal carriers. Being ≥ 2 years old, attending childcare center, presenting with any symptoms, having acute or chronic respiratory disease, and residing in a slum were associated with pneumococcal carriage. The most prevalent capsular types were 6C (14.5%), 15B/C (11.5%), 11A/D (9.2%), and 6A (7.6%). PCV10 serotypes represented 2.5%. All isolates were susceptible to levofloxacin, rifampicin, and vancomycin. Penicillin non-susceptible pneumococci (PNSP) comprised 39%, with penicillin and ceftriaxone MICs ranging from 0.12–8.0 μg/ml and 0.012–1.0 μg/ml, respectively. The 33 (28%) erythromycin-resistant isolates (MICs of 1.5 to >256 μg/ml) displayed the cMLSB (72.7%) or M (27.3%) phenotypes, harboring the erm (B) and/or mef (A/E) genes. High non-susceptibility rates (>20%) to clindamycin, erythromycin, penicillin, and tetracycline were largely explained by the prevalence of multidrug resistant (MDR) serotype 6C isolates. Conclusions: Effects of universal childhood PCV10 use on carriage were evident, with the near elimination of PCV10 serotypes. The emergence of MDR serotype 6C isolates, however, is a concern. Ongoing surveillance to monitor serotype 6C increase in invasive diseases is warranted.